Cardiac Tamponade by Hydatid Pericardial Cyst: A Rare Case Report - Kumar Paswan, Anil (Kowsar, 2013)
INTRODUCTION: Hydatid cysts are most commonly found in the liver and lungs but they are rarely found in pericardium. CASE PRESENTATION: We present a rare case of isolated hydatid cyst in pericardium of heart of a 70 year old female presented in casualty with unusual features like, dyspnea, palpitation and chest pain mimicking acute coronary syndrome. DISCUSSION: Hydatid cyst in Pericardium represents only 0.5-2% of cases of systemic echinoccocal infection. Isolated pericardial cyst is very rare in endemic region and may present mimicking acute coronary syndrome. Cardiac hydatid cysts should always be considered in presence of eosinophilia as present like acute coronary syndrome in endemic area.